(untitled) (Comprehensive Journal of Science, 2026)
This study develops an integrated analytical framework linking green transition, peacebuilding, and economic competitiveness in post-conflict Libya, addressing a significant gap in the sustainable development literature for fragile and conflict-affected states. Employing a mixed-methods research design, the study integrates secondary data analysis from international organizations, a SWOT-based assessment of Libya’s green economy potential, semi-structured interviews with 25 policymakers and experts, and scenario-building techniques to explore future transition pathways. The findings reveal substantial untapped potential in renewable energy, sustainable agriculture, and circular economy applications, and demonstrate that environmental sustainability can act as a catalyst for social stability and economic competitiveness. The proposed three-dimensional model identifies institutional reform, international cooperation, and community engagement as critical success factors. The study contributes a novel theoretical framework and provides actionable policy recommendations and measurable indicators to guide Libya’s environmental transition toward Vision 2035.